2021
DOI: 10.1152/ajplung.00042.2020
|View full text |Cite
|
Sign up to set email alerts
|

Lung metabolomics after ischemic acute kidney injury reveals increased oxidative stress, altered energy production, and ATP depletion

Abstract: Acute kidney injury (AKI) is a complex disease associated with increased mortality that may be due to deleterious distant organ effects. AKI associated with respiratory complications, in particular, has a poor outcome. In murine models, AKI is characterized by increased circulating cytokines, lung chemokine upregulation, and neutrophilic infiltration, similar to other causes of indirect acute lung injury (ALI)(e.g., sepsis). Many causes of lung inflammation are associated with a lung metabolic profile characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In recent years, an increasing number of studies have demonstrated that the development of ALI is related to inflammation, oxidative stress, apoptosis, and cellular immunity. [16][17][18][19] However, mortality due to ALI continues to be high. There are many published reports on the activity of natural products to treat ALI.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have demonstrated that the development of ALI is related to inflammation, oxidative stress, apoptosis, and cellular immunity. [16][17][18][19] However, mortality due to ALI continues to be high. There are many published reports on the activity of natural products to treat ALI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a significant decrease in renal function was also observed in patients with FEV1/FVC < 70%. Crosstalk between COPD and renal function can attribute to a complex mechanism containing inflammation [37,38]. The inflammatory mediators affect both lung and renal function [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggest that AKI induces metabolic alterations, for example, in the heart [138] or lung [139,140], possibly implicating metabolites in AKI–ALI. In mice subjected to bilateral ischaemia reperfusion injury, the metabolome of the remotely injured lung was examined by mass spectrometry 4 h after bilateral kidney ischaemia reperfusion injury and compared to sham operation.…”
Section: Mechanisms Of Acute Lung Injury After Akimentioning
confidence: 99%
“…Measurements of lung inflammation, lung MPO activity and lung KC/CXCL1 (‘IL8’) expression were elevated and peaked at 4 h after AKI, and lung ATP depletion had a nadir at 4 h. Lung ATP is to 80% produced by mitochondrial respiration (oxidative phosphorylation) and its depletion reports oxygen poor states and/or mitochondrial dysfunction. The most significant changes in the metabolome were detected at 24 h. Beyond ATP depletion, the analysis revealed evidence of alternative energy production and increased oxidative stress in the lung [140]. Whether the observed metabolic changes and/or altered metabolites act as AKI–ALI mediators and have a direct role in establishing or driving AKI–ALI or whether they are a result of interorgan crosstalk driven by other AKI–ALI mediators that signal between the kidney or extrarenal organs and the lung is unresolved to date.…”
Section: Mechanisms Of Acute Lung Injury After Akimentioning
confidence: 99%